Les systèmes innovants alimentaires, cas d’étude : la Ceinture Aliment Terre de Liège - Antonia D. Bousbaine; Christopher Bryant (Belgeo)
This article aims to understand the alternative food systems that are being set up in a particular territory, Wallonia, and more specifically in the Province of Liège. After reviewing existing alternative food systems and their characteristics, the article attempts to highlight the Walloon experiences that are taking place in the light of what is being constructed elsewhere. One case study is particularly highlighted, the Liege Food-Land Belt. This atypical case study is defined as a "dynamic of actors engaged in a project of an in-depth transformation of the local food system". This Belt is attempting to bring together all the alternative food actions that confront the dominant system, based on a healthier local agriculture that can feed the local populations. Its ultimate goal is to reconnect the city to its agricultural hinterland, in order to give a role to this agriculture in the context of its territory and to revitalize the local economy. A certain territorial food governance is beginning to emerge, which places the consumer / citizen at the centre of his diet.